(untitled) (Journal of Information Technologies in Education (ITE), 2010)
The paper presents the environment of demonstration of integrated environment for studying course «Basics of algorithmization and programming» (http://weboap.ksu.ks.ua), which allows execution of computational experiment to study the complexity and majorizability of sorting algorithms. We describe the design and development of new version of the application. Much attention is paid to the development component of the code editor, which will meet the current requirements of tools to write programs.